Job Displacement, Family Dynamics and Spousal Labor Supply - Martin Halla; Julia Schmieder; Andrea Weber (Institute of Labor Economics (IZA), 2018)
We study interdependencies in spousal labor supply and the effectiveness of intrahousehold insurance in a sample of married couples, where the husband loses his job due to a mass layoff or plant closure using data from the Austrian Social Security Database. We show that in our sample of relatively young couples the shock hits households at crucial stages of family formation, which requires careful modeling of the wives' counterfactual lifecycle labor market patterns. In our empirical analysis, we propose three independent control groups of unaffected households to identify the causal effects of husbands' displacement on wives' labor supply. Our empirical results show that husbands suffer large and persistent employment and earnings losses over the first 5 years after displacement. But wives' labor supply increases only moderately and they respond predominantly at the extensive margin. The implied participation elasticity with respect to the husband's earnings shock is very small, about -0:04. While the wives' earnings gains recover only a tiny fraction of the household income loss, public transfers and taxes are a more important insurance at least in the short run. In terms of non-labor market related outcomes, we find a small positive effect on the probability of divorce, but no effect of the husband's job displacement on fertility. The presence and ages of children in the household are crucial determinants of the wife's labor supply response. The most responsive group are mothers, who are planning to return to the labor market after a maternity break, while mothers of very young children or wives without children remain unresponsive. We thus conclude that Austria's strong gender identity norms are an explanation for the limited scope of intra-household insurance.
Keywords: D19; J22; J65; 330; firm events; household labor supply; intra-household insurance; added worker effect